Teeth staining by green propolis extract: in vitro assay (Research, Society and Development, 2023)
In dentistry, propolis has aroused interest due to its satisfactory results obtained in several specialties. The aim of this study was to verify whether the green propolis extract applied at concentrations of 17% and 21% on the exposed dentin of healthy bovine teeth were capable of promoting a staining effect on the respective tooth structure. This is an experimental study where 40 crowns of healthy bovine teeth were cut in half, in an axial cut, in the mesiodistal direction, in order to expose the dentin. The specimens were enumerated and randomly divided into four groups (G1 to G4) for acid etching to simulate hypersensitive dentin, and subsequently application of green propolis extract solutions, used as possible obliterating agents in the treatment of dentin hypersensitivity, being: Group 1 (G1): 37% phosphoric acid and 17% propolis extract without brushing, Group 2 (G2): 37% phosphoric acid and 21% propolis extract without brushing, Group 3 (G3): 37% phosphoric acid and 17% propolis extract with brushing and Group 4 (G4): 37% phosphoric acid and 21% propolis extract with brushing. In the week following the application of the propolis extracts, the teeth were submitted to a prophylaxis procedure and it was observed that in all of them the solution remained fixed, conferring a staining effect both on the dentin and on the enamel of the teeth. same. It can be concluded that the green propolis extracts provided a staining effect on the studied bovine teeth.